The outcome of out-of-hospital cardiac arrest based on the etiology of cardiac arrest; A scoping review - Sedigheh Shaeri; Julie Considine; Katie N. Dainty; Theresa Mariero Olasveengen; Laurie J. Morrison (PLoS ONE, 2025)
Background Disparity is believed to exist between generic Utstein etiological classifications of 2004 and 2015 when compared with confirmed etiologies, but the impact of this disparity on reported survival outcomes is unknown. Objective This scoping review was proposed with two objectives: 1-to report outcomes based on confirmed etiology of OHCA in comparison with Utstein classified etiologies and 2- to identify outcomes of OHCA by etiology following cause-targeted interventions. Method Medline, Embase, and EBM- Cochrane databases were searched from inception to 2024. Studies were selected if included population was adults with OHCA for whom survival outcomes of OHCA were reported based on the confirmed etiology compared to Utstein etiological classification (2004 or 2015) or reported based on the etiology following cause-targeted interventions. A descriptive review of included studies was conducted. Result The search yielded 24,833 citations. Thirty-nine studies met inclusion criteria. These articles were predominantly published in Europe and North America between 2010–2024. The Utstein etiological classification was used in all studies (Utstein 2004; n = 31, Utstein 2015; n = 8). Survival to discharge was higher for drug overdose induced OHCA than presumed cardiac etiologies (9–83% vs 8.3–63%). For confirmed etiology of drowning, 30-day survival was higher than the rate reported by presumed cardiac etiologies (Utstein 2004) (11.5% vs 8.8%) while survival to discharge was lower following confirmed etiologies of trauma (1.7–5.1% vs 8–12%), hanging (3.3–43% vs 12–61%), respiratory disease (5% vs 9%), and intracranial hemorrhage (ICH) (11% vs 40%) compared with Utestin etiological classifications (2004 or 2015). Thrombolysis therapy resulted in better 30-day survival compared to placebo for OHCA due to presumed pulmonary embolism (16% vs 6%; p = 0.05), and conventional resuscitation resulted in higher survival for OHCA due to drowning (10.5% vs 8.6%) or respiratory disease (6.8% vs 4.54%) versus chest compression only. Conclusion The reported survival outcomes for confirmed non-cardiac etiologies is inconsistent across studies compared with Utstein etiological classifications of 2004 or 2015. Better survival outcomes following few cause-targeted interventions may be attributed to etiologically well-defined patient cohorts. More vigorous case selection based on etiology may refine the reported outcomes and comparisons with interventions across published studies.